2021
DOI: 10.1126/science.abd8700
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of fold switching in a metamorphic protein

Abstract: Metamorphic proteins switch between different folds, defying the protein folding paradigm. It is unclear how fold switching arises during evolution. With ancestral reconstruction and nuclear magnetic resonance, we studied the evolution of the metamorphic human protein XCL1, which has two distinct folds with different functions, making it an unusual member of the chemokine family, whose members generally adopt one conserved fold. XCL1 evolved from an ancestor with the chemokine fold. Evolution of a dimer interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 56 publications
3
73
0
Order By: Relevance
“…6 Human lymphotactin (a.k.a. XCL1) iso-energetically populates two β-sheet conformations with completely different hydrogen bonding patterns 7,8 and is associated with autoimmune disorders. 9 Furthermore, human Chloride Intracellular Channel 1 (CLIC1) remodels its secondary structure and changes its function from a glutathione reductase 10 to a chloride channel 11 that balances intracellular chloride levels when cells undergo oxidative stress due to cancer 12 or Alzheimer's.…”
Section: Introductionmentioning
confidence: 99%
“…6 Human lymphotactin (a.k.a. XCL1) iso-energetically populates two β-sheet conformations with completely different hydrogen bonding patterns 7,8 and is associated with autoimmune disorders. 9 Furthermore, human Chloride Intracellular Channel 1 (CLIC1) remodels its secondary structure and changes its function from a glutathione reductase 10 to a chloride channel 11 that balances intracellular chloride levels when cells undergo oxidative stress due to cancer 12 or Alzheimer's.…”
Section: Introductionmentioning
confidence: 99%
“…One counterexample is the intrinsic disorder found in a significant number of functional proteins and protein regions. These intrinsically disordered regions do not adopt a stable three-dimensional structure, instead existing as conformational ensembles of states that may include pre-formed structural nuclei (Dyson, 2016). Other counterexamples are provided by proteins which interconvert among multiple folded states, ranging from a "fragile fold", in which substitution of a few amino acids -even one -results in the domain co-existing in two states Ha and Loh, 2012) to the general concept X.…”
Section: Introductionmentioning
confidence: 99%
“…In metamorphic proteins, which can be considered an extreme case of a fragile fold, an even greater number of hydrogen bonds differ between the two folds as seen in lymphotactin (which alternates between a conventional chemokine fold and a dimeric β sandwich; Kuloglu et al, 2002;Tuinstra et al, 2008). These studies suggest that protein folds may hide unforeseen flexibility or fragility which can be trivially accessed by small changes in sequence or environmental conditions, facilitating the evolution of new folds and protein domains (Yadid et al, 2010;Tuinstra et al, 2008;Alexander et al, 2009;Dishman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent decades, proteins have been discovered that defy this norm, folding into multiple different structures and reversibly interconverting between them. Recent work has shown that these proteins, called metamorphic proteins, may be more common than initially expected [ 8 , 9 ]. Interest in the biological relevance of metamorphic protein folding is growing, and efforts to understand and harness protein metamorphosis for therapeutic benefit are beginning to mount [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%